Implementación de un sistema de inteligencia de negocios. Escuela de Ciencias de la Administración UNED (Revista Electrónica Calidad en la Educación Superior, 2021)
Business intelligence is a relevant concept in the business field. Thanks to the current technology achievements, there are a new broader set of options that allows to establish direct contact with internal and external clients of the organization and provide key information that helps the decision making and strategic planning processes. Universities are no exception to these global changes, and it has turn increasingly necessary to implement Business intelligence tools to optimize all the resources available, to measure and accomplish the organization KPI´s. This article presents an experience on the implementation of a Business Intelligence system in the UNED´s Costa Rica Business School. The experience began in 2020 as a project, with the goal of detecting the needs that this type of system must address. The results came through a mixed methodology and the use of different applied online instruments on the sectors involved (professional sector, students, and specialist in the field). Among the main findings stands the relevance of the implementation of this technological alternative, as well as the fact of having a platform for its proper management. It is also important that the organization is prepared at a technical and cultural level to be able to implement the BI solution.